2022
DOI: 10.31620/jccc.06.22/08
|View full text |Cite
|
Sign up to set email alerts
|

Does Environmental Awareness via SNSS Create Sustainable Consumption Intention Among the Millennials?

Abstract: Globalization as well as digitalization is changing not only the business formats but also the environmental scenario of this planet. It is quite imperative to move society towards sustainable consumption. As social networking sites are believed to be capable of influencing users’ perspectives, their role in creating sustainable consumption intentions must be explored. This research, thus, explores the impact of Environmental Awareness via Social Networking Sites (SNSs) and Environmental Concerns on Green Prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The effect of environmental anxiety on the likelihood of making a purchase of a green product. This study's results lend credence to the working hypothesis by showing that there is a statistically significant correlation between the two independent variables (Shamsi et al, 2022). According to the results, people's intentions and actions towards the purchase of eco-friendly products were significantly influenced by their sense of behavioral control.…”
Section: Results Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The effect of environmental anxiety on the likelihood of making a purchase of a green product. This study's results lend credence to the working hypothesis by showing that there is a statistically significant correlation between the two independent variables (Shamsi et al, 2022). According to the results, people's intentions and actions towards the purchase of eco-friendly products were significantly influenced by their sense of behavioral control.…”
Section: Results Discussionsupporting
confidence: 73%
“…Findings from this study provide statistical support for the null hypothesis that there is a connection between environmental concern and an interest in purchasing eco-friendly goods. There is a strong correlation between people's environmental concerns and their willingness to purchase environmentally friendly products (Shamsi et al, 2022). H4: Green awareness significantly impacts on green consumer intention.…”
Section: Green Awareness Green Consumer Intention and Green Consumer ...mentioning
confidence: 99%
“…This means that the greater the environmental awareness, the greater the ecological consumption behavior of consumers [ 61 ]. Similarly, it has been shown that care for the environment and environmental consciousness substantially affect the desire to buy ecological products [ 62 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The EV industry in India recovered fast from the slowdown caused by pandemic in 2020 expected to grow at a CAGR of 49% between 2021 and 2030 (India Energy Storage Alliance (IESA), 2022a). This is driven by factors such as rising fuel prices, entry of new players, advancement in EV technology, continued subsidy support from both the central and state governments, implementation of emission standards and the rising consciousness about the global warming and climate change, and so forth, which is translating into the growing social acceptance (Salman Shamsi et al, 2022) and adoption of EVs (India Energy Storage Alliance (IESA), 2022b). Any global business sector that prioritizes responsibility towards customers, society and environment, builds on innovation and ensures sustainable development is expected to bring equitable and inclusive growth that takes care of the needs of all the stakeholders (Chandrasekaran, 2022).…”
Section: Social Acceptancementioning
confidence: 99%